2016
DOI: 10.1093/dnares/dsw037
|View full text |Cite
|
Sign up to set email alerts
|

Draft genome sequence of an inbred line ofChenopodium quinoa, an allotetraploid crop with great environmental adaptability and outstanding nutritional properties

Abstract: Chenopodium quinoa Willd. (quinoa) originated from the Andean region of South America, and is a pseudocereal crop of the Amaranthaceae family. Quinoa is emerging as an important crop with the potential to contribute to food security worldwide and is considered to be an optimal food source for astronauts, due to its outstanding nutritional profile and ability to tolerate stressful environments. Furthermore, plant pathologists use quinoa as a representative diagnostic host to identify virus species. However, mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
104
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(107 citation statements)
references
References 83 publications
3
104
0
Order By: Relevance
“…Pseudomolecules (hereafter referred to as chromosomes, which are numbered according to a previously published single-nucleotide polymorphism (SNP) linkage map 13 ) were created by anchoring 565 scaffolds to the linkage map, representing 1.18 Gb (85%) of the total assembly length ( Table 1, Supplementary Data 1, Supplementary Data 2). This assembly represents a substantial improvement over the previously published quinoa draft genome sequence, which contained more than 24,000 scaffolds with 25% missing data 14 .…”
Section: Sequencing Assembly and Annotationmentioning
confidence: 96%
“…Pseudomolecules (hereafter referred to as chromosomes, which are numbered according to a previously published single-nucleotide polymorphism (SNP) linkage map 13 ) were created by anchoring 565 scaffolds to the linkage map, representing 1.18 Gb (85%) of the total assembly length ( Table 1, Supplementary Data 1, Supplementary Data 2). This assembly represents a substantial improvement over the previously published quinoa draft genome sequence, which contained more than 24,000 scaffolds with 25% missing data 14 .…”
Section: Sequencing Assembly and Annotationmentioning
confidence: 96%
“…Its genomic complexity and polyploid nature have made molecular genetic analyses of the genetic mechanisms underlying its salt tolerance traits challenging. However, the draft genome of C. quinoa that was recently made available will be an excellent resource opening new paths to explore its stress adapted biology (Yasui et al, 2016). Also, the genome of the closely related non-halophyte Beta vulgaris (Amaranthaceae) and additional transcriptomes of the halophytic but non-salt gland subspecies B. vulgaris ssp.…”
Section: New Genetic Resources and Tools Provide Insights Into The Momentioning
confidence: 99%
“…Betacyanins can be further modified by betalain-related glucosyltransferases that catalyse the 5-O-glucosylation of cyclo-DOPA (Sasaki et al, 2005) or alternatively the 5-O-or 6-O-glucosylation of betanidin (Figure 1a, Das et al, 2013;Vogt, 2002;Vogt et al, 1999). Recently, our group and others sequenced the quinoa genome (Jarvis et al, 2017;Yasui et al, 2016;Zou et al, 2017), and based on these genomic data, we identified the genes responsible for betalain biosynthesis including CqCYP76AD1, CqDODA and CqCDOPA5GT (Imamura et al, 2018).…”
Section: Introductionmentioning
confidence: 99%